Resistance to FLT3 inhibitors involves different molecular mechanisms and reduces new DNA synthesis - Jingmei Yang; Ran Friedman (Biochemistry and Biophysics Reports)
Acute myeloid leukaemia (AML) is a hard to treat blood cancer. Mutations in FLT3 are common among the genetic aberrations that characterise the cancer. Patients initially react to FLT3 inhibitors but drug resistance is a hinder to successful therapy. To better understand the mechanisms leading to drug resistance, we generated four AML cell lines resistant to the inhibitors gilteritinib or FF-10101, and explored their resistance mechanisms. We further tested whether the novel inhibitor Chen-9u could be used to limit cell growth. The results showed that each of the four resistant cell lines became resistant through a different mechanism. Resistant cells showed decreased FLT3 and increased NRAS pathway activity and reduced DNA synthesis due to decrease in CDK4 activity. Resistance mechanisms included resistance mutations in FLT3 (C695F and N701K), and a novel mutation in NRAS (G12C). In a fourth line, resistance might have developed through a MYCN mutation. Cell growth was inhibited by Chen-9u and resistant clones could not be obtained with this inhibitor. The results highlight opportunities and limitations. On the one hand, resistant cells were produced due to different mechanisms, showing the versatility of tumour cells. Furthermore, resistance developed to the most advanced inhibitors, one of which is covalent and the other non-covalent but highly specific. On the other hand, it is shown that DNA synthesis is reduced, which means that resistance has evolutionary consequences. Finally, the novel drug-resistant cell lines may serve as useful models for better understanding of the cellular events associated with inherent and acquired drug resistance.